Academic Writing Development at the University Level: Phrasal and Clausal Complexity Across Level of Study, Discipline, and Genre. (April 2016) - Staples, Shelley; Egbert, Jesse; Biber, Douglas; Gray, Bethany
Using the British Academic Written English corpus, this study focuses on the use of grammatical complexity features in university level texts written by first language (L1) English writers to demonstrate knowledge and perform other specialized tasks required of advanced academic writers. While the primary focus of the analysis is on writing development from first-year undergraduate to graduate students, we also consider interactions with discipline and genre. The study goes beyond most previous work on grammatical complexity in writing by investigating the use of phrasal as well as clausal features. The results show that as academic level increases, the use of phrasal complexity features in writing also increases. On the other hand, the use of clausal complexity features in student writing, particularly finite dependent clauses, decreases as academic level increases. Results further indicate that the extent of the differences across level is mediated by discipline and genre, reflecting patterns observed in research on disciplinary variation in professional academic writing.